Eleventh Five Year Plan 2007-2012 and Annual Plan 2007-08 Government of Punjab - Planning Commission (Planning Commission, 2007)
The economy of Punjab has traditionally revolved around its success in the agriculture sector. Since the Green Revolution in the 1960s, Punjab has taken major strides in increasing agricultural productivity and has the unique distinction of contributing the maximum quantities (75% wheat and 30% rice during marketing season 2006-07) to the central pool of foodgrains. Almost two decades of militancy in the State, however, retarded the expansion of the manufacturing sector in the State while some of its neighboring States expanded their industrial production given their locational advantages or a more conducive policy regime.
Government of Punjab, Department of Planning